This week we learned how to find a solution by using substitution

As an example i will find the solution to 5x-3y=27 and 2x+y=2

the first step is to use one of the equations and isolate one of the variable to one side so 2x+y=2 will turn into y=-2x+2

no we have what y is equal to so step two would be to put y into the other equation so 5x-3y=27 turns into 5x-3(-2x+2)=27

step 3 is to use distributive property to get rid of the brackets so 5x-3(-2x+2)=27 turns into 5x+6x-6=27

step 4 is to combine like terms so 5x+6x-6=27 turns into 11x-6=27

step 5 is to cancel out terms, in this case this means adding 6 to both sides 11x=33

step 6 is to divide to get x by itself

11x/11 33/11

x=3

now that we have x we need to put x into our equation from step one

y=-2(3)+2

now get rid of the brackets

y=-6+2

y=-4

now that we have X and Y we know our solution

(3,-4)

## Leave a Reply